2006
DOI: 10.1590/s1516-89132006000100001
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the germination of spores among and within natural populations of the endangered tree fern Dicksonia sellowiana Hook. (Xaxim)

Abstract: The objective of this study was to analyze the existing variability in the germination of individuals' spores collected from two natural populations of Dicksonia sellowiana in southern Brazil. The largest intrapopulational variation was observed for the spores germination. These results suggested the existence of adaptative strategies that favored the gradual and continuous entrance of new individuals into the gametophytic population.The behavior of the individuals of the species within each population followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…On the other hand, the spores of Ophioglossum palmatum L. germinate better in strong acid conditions, and the germination is reduced or eliminated in acid or slightly neutral conditions (Whittier 1981,Whittierand andMoyroud 1993). For the spores of Cheilanthes feei T. Moore (Polypodiaceae), higher germination percentages were observed in acidic pH ( 4.5 and 5.5) (Nondorf et al 2003).This work showed that the germination percentage of G. pectinata spores was very low in comparison to several other fern species that could reach around 100% of spore germination as reported by Gomes et al (2006) for spores of Dicksonia sellowiana Hook. (Dicksoniaceae).…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, the spores of Ophioglossum palmatum L. germinate better in strong acid conditions, and the germination is reduced or eliminated in acid or slightly neutral conditions (Whittier 1981,Whittierand andMoyroud 1993). For the spores of Cheilanthes feei T. Moore (Polypodiaceae), higher germination percentages were observed in acidic pH ( 4.5 and 5.5) (Nondorf et al 2003).This work showed that the germination percentage of G. pectinata spores was very low in comparison to several other fern species that could reach around 100% of spore germination as reported by Gomes et al (2006) for spores of Dicksonia sellowiana Hook. (Dicksoniaceae).…”
Section: Discussionsupporting
confidence: 59%
“…However, tree ferns produce billions of spores (Large & Braggins, 2004); D . sellowiana , for example, produces approximately 4 billion spores per kilogram (Gomes et al, 2006), which facilitates the formation of spore banks (Fiilippini et al, 1999). Moreover, it has been suggested that in general they are able to disperse even over distances greater than 3000 km (Tryon, 1970; Tryon & Tryon, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Germination and establishment are crucial stages in the life cycle of a plant [13,14] especially for the bryophytes which must survive an array of habitat conditions mainly on only one set of chromosomes. Germination of bryophyte spores has been reported to be limited by habitat pH.…”
Section: Discussionmentioning
confidence: 99%